Systematic approaches to a successful literature review - Booth, Andrew (Sage, 2016)
Showing you how to take a structured and organized approach to a wide range of literature review types, this book helps you to choose which approach is right for your research. Packed with constructive tools, examples, case studies and hands-on exercises, the book covers the full range of literature review techniques.